Parenteral Acute Viral Hepatitis B and C: Modern Diagnosis, Prevention, and Treatment - Nomozovich, Rakhmonov Ravshan (Journal of Science in Medicine and Life, 2024)
Questions of diagnostics, feature of clinic, treatment and preventation of active virus hepatites with parenteral mechanism of transmission of an infection (hepatites B, C, ) which make up a significant number of all acute virus hepatites are considered. A wide circulation, features of modern diagnostics and frequency of progress of chronic forms defi ne a problem of diagnostics and treatment of a virus hepatites,as one of important for domestic healthcare.Data about the importance and features serological markers of viruses of a hepatites B, C, , are presented and their clinical interpretation is analyzed. Modern drug therapy is in detail resulted including preparations of interferon. The need of specific preventive actions, post-exposure preventive maintenance and passive immunization is considered.